Implementation of Learning Evaluation Based on Jean Piaget's Cognitive Development Stages in Islamic Religious Education - Sukarni, Iskandar; Lubna, Lubna; Supardi, Supardi (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
Assessment in Islamic Religious Education (PAI) holds a crucial role, not only as a measure of academic achievement but also as a means for internalizing Islamic values. However, in practice, evaluations in the field often neglect to consider the stages of students' cognitive development, resulting in a mismatch between the form of evaluation and students' readiness to think. This study aims to examine the implementation of Jean Piaget's cognitive development theory in the design of PAI learning assessments, with a focus on its principles, forms, benefits, and challenges. The method employed is library research using a qualitative approach. Data were obtained from relevant literature and critically analyzed through a hermeneutic approach. The findings indicate that a Piaget-based assessment approach requires the adjustment of instruments according to students' cognitive characteristics at each stage: symbolic and intuitive for the preoperational stage, concrete and contextual for the concrete operational stage, and analytical and reflective for the formal operational stage. Cognitively appropriate evaluations have been proven to enhance learning effectiveness, increase learning motivation, and strengthen the development of students' Islamic character. Nevertheless, its implementation faces challenges in terms of teacher readiness, availability of media, and time constraints. Thus, this approach encourages the need for transformation in PAI assessment practices to become more humanistic, progressive, and aligned with children's psychological development. Keywords: Character development, cognitive development, Islamic Religious Education, Jean Piaget, learning assessment.